Adenosine Triphosphate Content and Seed Vigor - Ching, Te May (1973)
ATP content in imbibed seeds is significantly correlated with seedling size in fatty, starchy and proteinaceous seeds, and it indicates viability in seed lots. ATP content thus appears to be a useful biochemical index of seed vigor.